2017
DOI: 10.26417/ejser.v10i1.p16-27
|View full text |Cite
|
Sign up to set email alerts
|

Analysis Effect of Service Quality, Educational Facilities, and Method of Learning, Student Satisfaction and Loyalty to Students - Studies in the University of Widyatama Bandung

Abstract: This study aimed to analyze the effect of service quality, education facilities, and teaching methods in conjunction with student satisfaction and loyalty Widyatama University students. The research was conducted by survey method, the data obtained by distributing questionnaires to students. The study population was a student Of the Faculty of Business and Management, University of Widyatama. Data were analyzed using Structural Equation Modeling (SEM) with AMOS. From these results it can be concluded that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
3
2
0
4
Order By: Relevance
“…It is in line with the result of the hypothesis testing that service quality positively and significantly influenced student satisfaction in Senior High School Education. The finding of this study is in line with a study by (Annamdevula & Bellamkonda, 2016;Appuhamilage & Torii, 2019;Azam, 2018;Bakrie et al, 2019;Chandra et al, 2018;Dora, 2017;Hassan et al, 2019;Jabbaret al, 2020;Jiewanto et al, 2012;Leonnard et al, 2014;Lunarindiah, 2018;Munizu & Hamid, 2015;Mansari et al, 2014;Permana et al, 2020;Wulandari & Suryani, 2017). The service quality provided by Senior High School Education exceeded the students' expectations that made the students felt satisfied.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It is in line with the result of the hypothesis testing that service quality positively and significantly influenced student satisfaction in Senior High School Education. The finding of this study is in line with a study by (Annamdevula & Bellamkonda, 2016;Appuhamilage & Torii, 2019;Azam, 2018;Bakrie et al, 2019;Chandra et al, 2018;Dora, 2017;Hassan et al, 2019;Jabbaret al, 2020;Jiewanto et al, 2012;Leonnard et al, 2014;Lunarindiah, 2018;Munizu & Hamid, 2015;Mansari et al, 2014;Permana et al, 2020;Wulandari & Suryani, 2017). The service quality provided by Senior High School Education exceeded the students' expectations that made the students felt satisfied.…”
Section: Discussionsupporting
confidence: 89%
“…The higher the student satisfaction against the services provided by the company, the student loyalty would increase more. It is in line with a study by (Africia et al, 2017;Annamdevula & Bellamkonda, 2014;Appuhamilage & Torii, 2019;Chandra et al, 2018;Dharmayanti et al, 2018;Dora, 2017;Hassan et al, 2019;Leonnard et al, 2014;Munizu & Hamid, 2015;Shahsavar & Sudzina, 2017;Wulandari & Suryani, 2017). However, it is in contrast to a study by (Bakrie et al, 2019;Ismanova, 2019;Lunarindiah, 2018).…”
Section: Literature Reviewsupporting
confidence: 90%
See 1 more Smart Citation
“…A study concluded that the learning environment (classrooms, teaching aids, libraries) and infrastructure (dormitory, sports facilities, parking & transportation) also contributed positively to student achievement (Zurainan, 2016). Previous literature has also shown that the availability of good and quality supporting facilities could increase student satisfaction (Dora, 2017;Napitupulu et al, 2018;Hasan & Hosen, 2020). Kotler and Keller (2009) stated that satisfaction is an individual's liking/dislike of a product after comparing product quality with expectations.…”
Section: Facilitymentioning
confidence: 99%
“…In a service business, all existing facilities that provide facilities, integrity, interior design and facilities should be considered, especially those closely related to what consumers directly perceive or obtain (Dora, 2017). Tangible substances are elements that can be "seen" and "moved" by students in university services (Afshan, 2018).…”
Section: Tangiblesmentioning
confidence: 99%